Women's Contribution to Religious Moderation in a Multicultural Society: a Study in Balun Village, Lamongan - Miftakhul Muthoharoh; Khoirotun Ni’mah (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2025)
Indonesia’s multicultural society, characterized by ethnic, cultural, and religious diversity, is vulnerable to intergroup friction, especially given the strong religious convictions of its people. Building multicultural awareness through moderate religious practices is therefore crucial. Balun Village, recognized as the “village of Pancasila” for its strong pluralism, exemplifies this effort. This research investigates the role of women in fostering religious moderation and explores the social construction of women’s involvement in Balun Village. Employing a qualitative phenomenological approach, data were gathered through observation, interviews with religious, community, and women leaders of various backgrounds, and documentation from village authorities and related organizations. Data analysis followed the Miles & Huberman technique, encompassing data reduction, display, verification, and conclusion drawing. Findings reveal that women play a strategic role in promoting religious moderation across multiple domains. Within families, women serve as educators of tolerance, instilling diversity values in children from an early age. Socially, they participate in inclusive religious and community activities and act as mediators in interfaith groups to maintain harmony. Additionally, women help preserve local culture as a unifying force amid pluralism. Their influence is evident in interfaith economic initiatives, the internalization of moderation values in family education, and their leadership in religion-neutral social activities. Through active engagement, women in Balun Village significantly contribute to creating a harmonious and moderate society.